2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.104938
|View full text |Cite
|
Sign up to set email alerts
|

Call to Action: SARS-CoV-2 and CerebrovAscular DisordErs (CASCADE)

Abstract: tized during the global crisis. It will also guide public health guidelines for at-risk populations to reduce risks of complications from such comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
0
34
0
3
Order By: Relevance
“…Future studies such as CASCADE (Call to Action: SARS-CoV-2 and Cerebrovascular DisordErs) are required to shed light on changes in stroke care protocols and hospitalization rate during the pandemic. [84] Our study reported patients with intracranial hemorrhage. Among the patients with SAH-23, no aneurysm was detected in 69.5% patients, which is higher than reported 15%(5%-34%) spontaneous SAH among patients without SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 86%
“…Future studies such as CASCADE (Call to Action: SARS-CoV-2 and Cerebrovascular DisordErs) are required to shed light on changes in stroke care protocols and hospitalization rate during the pandemic. [84] Our study reported patients with intracranial hemorrhage. Among the patients with SAH-23, no aneurysm was detected in 69.5% patients, which is higher than reported 15%(5%-34%) spontaneous SAH among patients without SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 86%
“…Increased risk of adverse outcomes and patient safety in hospitalized cases with dementia has been a challenging condition even prior ot COVID-19 pandemic [31]. A high mortality rate of COVID-19 among demented patients could be partially explained by ageing and chronic comorbidities, particularly cardio or cerebr-vascular diseases [32,33]. In addition, using the UK Biobank databasebase and after adjusting for pre-existing dementia, cardiovascular diseases, and type-2 diabetes, Kuo et al showed that the ApoE e4e4 allele is associated with severe COVID-19 infection [34].…”
Section: Discussionmentioning
confidence: 99%
“…The CASCADE (Call to Action: SARS-Cov-2 and CerebrovAscular DisordErs) study is a worldwide, multicentre hospital-based study on stroke incidence and outcomes during the COVID-19 pandemic. 45 The main aim of this study is to enable the understanding of the changes in models of stroke care, differential hospitalization rate, and stroke severity, as it pertains to the COVID-19 pandemic.…”
Section: What Are the Preliminary Data Of The Current Sars-cov-2 Outbmentioning
confidence: 99%
“…5 In light of those data, several stroke centres have come together to design a study protocol with the aim to investigate the worldwide burden of cerebrovascular disease before, during and after SARS-CoV-2 pandemic (CASCADE study). 45 In addition, stroke centres have been guided to implement a 'protected code stroke' for the management of acute stroke patients. 50,52 'Protected code stroke' actually originates from the acknowledgment that every stroke patient is potentially infected and should be treated accordingly.…”
Section: What Is the Impact Of Covid-19 Pandemic On The Health Care Omentioning
confidence: 99%